Hellquist's Swedish etymology - Språkbanken Text (University of Gothenburg, 2024)
Hellquist's Swedish etymology

Hellquists Svensk etymologisk ordbok
Hellquists Svensk etymologisk ordbok
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik